2012
DOI: 10.1001/jama.2011.2034
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Vaccine Antibody Concentrations in Children Exposed to Perfluorinated Compounds

Abstract: Context Perfluorinated compounds (PFCs) have emerged as important food contaminants. They cause immune suppression in a rodent model at serum concentrations similar to those occurring in the US population, but adverse health effects of PFC exposure are poorly understood. Objective To determine whether PFC exposure is associated with antibody response to childhood vaccinations. Design, Setting, and Participants Prospective study of a birth cohort from the National Hospital in the Faroe Islands. A total of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
563
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 592 publications
(606 citation statements)
references
References 26 publications
20
563
1
3
Order By: Relevance
“…Prenatal exposure is associated with childhood exposure to PFASs as a major source of postnatal exposure is through breastfeeding. Further, previous studies have found the childhood serum-PFAS concentrations to be associated with reduced antibody concentrations after routine childhood vaccination at age 5 (Grandjean et al 2012). Thus, it would be interesting to include PFAS levels in child serum in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal exposure is associated with childhood exposure to PFASs as a major source of postnatal exposure is through breastfeeding. Further, previous studies have found the childhood serum-PFAS concentrations to be associated with reduced antibody concentrations after routine childhood vaccination at age 5 (Grandjean et al 2012). Thus, it would be interesting to include PFAS levels in child serum in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, prenatal exposures were previously found to affect vaccine responses at age 5 years, but not in older children (Grandjean et al 2012) and hospitalization rates in children up to age 11 years may have been affected by unknown postnatal exposures as well as a variety of other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may cause susceptibility for infections, preeclampsia or thrombocytopenia in the mother, and ultimately can have foetal consequences in relation to abortus habitualis, intrauterine growth retardation and preterm delivery [27,28]. Furthermore, the prenatal exposure to POPs, especially PFASs, can lead to suppressed immune responses in early childhood [711,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…These studies were among the first to evaluate the ability of PFAS to modulate immune function in humans. In one study of children from the Faroe Islands, a population that relies heavily on marine mammals contaminated with a variety of persistent organic pollutants, including PCBs and perfluorinated compounds, Grandjean et al (2012) reported that pre-natal and post-natal serum concentrations of both PFOA and PFOS were negatively associated with responses to diphtheria and tetanus vaccination in 5-7 year old children, although different patterns for the two PFASs did exist across contaminants, vaccines, and ages. In a separate study based on the Norwegian Mother and Child Cohort Study, Granum et al (2013) reported a negative association between maternal serum concentrations of PFOA and PFOS and the response to rubella immunization in 3-year-old children.…”
mentioning
confidence: 99%